Knowledge, attitudes, and perceptions towards pneumococcal vaccines among adults in the United States - Salini Mohanty; Jui-Hua Tsai; Ning Ning; Ana Martinez; Rishi P. Verma; Bianca Chun; Kelly D. Johnson; Nicole Cossrow; M.Doyinsola Bailey; Thomas Weiss; Elmira Flem; Jordana K. Schmier (Expert Review of Vaccines)
Objectives The attitudes and perceptions of healthcare consumers (HCCs) are increasingly becoming more relevant in decision-making with healthcare providers and incorporated into healthcare decision-making by national immunization technical advisory groups and health technology assessment agencies. With newer pneumococcal vaccine options available, HCCs’ attitudes and perceptions play a key role in gauging potential acceptance. The objective of this study was to assess HCCs’ knowledge, attitudes, and perceptions toward pneumococcal vaccines for adults.Methods Between March and May 2024, eligible U.S. adult HCCs were invited to participate in an online survey focusing on experiences and attitudes toward vaccines.Results Among 141 participating HCCs, average age was 53.1 years. The majority of participants were male (51.1%) and 64.5% identified as White. Most HCCs received at least one vaccine in the past year (81.6%). HCCs most often received vaccines at medical offices and pharmacies. HCCs supported lowering the age-based pneumococcal vaccine recommendation to all adults 50 years and older and were willing to receive a supplemental pneumococcal vaccine dose following completion of the recommended series for additional protection.Conclusions These findings indicate that new adult pneumococcal vaccines would be accepted and valued by HCCs if recommended by HCPs.